Quality review of power for lighting system of signaling installations in Bogota, Colombia - Parra Martínez, Carlos Andrés; Serrato Vanegas, Hugo Alejandro; Rodríguez Molano, José Ignacio (Ingeniería Solidaria, 2016)
Introduction: This article is a case study of the project “Energy quality directed to harmonic values in the lighting systems used in traffic light intersections of the city of Bogota, D. C.”. The project was conducted during the year 2015 by the Universidad Distrital Francisco Jose de Caldas. Methodology: The measurements were directed to harmonic distortions and power factors in the lighting systems -type led in Bogota, incandescent and halogen, to contrast with the recommended thd levels for every type in iec 61000-3-2. A digital meter, model everfine pf9811, was used in the analysis. Results: Significant harmonic distortion and encumbrance of the grid were determined when using the new led lighting system, which renders a significant drop in energy quality with which the control equipment operates. Discussion: Technical challenges are evidenced for the start-up of intersections due to electromagnetic disturbances that affect the electric grid caused by new lighting technologies. Because of that, the electromagnetic disturbances in the electric grid must be mitigated or eradicated. The conclusion and recommendation of the case study is the observation of existent base values in this article and in new research.